THE THREAT OF COVID-19 PANDEMIC IN SOCIAL NETWORK-THINKING - Nurisnaeny, Poppy Setiawati; Prasetya, Rendy Ananta; Suwedi, Suwedi (International Review of Humanities Studies, 2023)
The COVID-19 pandemic creates various dynamics of uncertainty that impact morbidity, mortality, and economic damage. The dynamics of these threats are expanding in the globalization era through networks and national security into a multidimensional sphere that tends to be unpredictable (Starvridis, 2015). Social transformation is always marked with certainties. Therefore, scientific regulations are needed to guide various operations, which functions as a principle in adapting to the quick-changing socio-cultural dynamics. This study aims to analyze the threat of the Covid-19 pandemic and strategic thinking steps in the ethnographic framework of social network thinking. This research uses a descriptive qualitative method with an ego-centric network approach. The research results show that through the network framework, it is possible to see threats that are relatively different from those that have existed so far (mainstream). Interhuman relationships and interactions between humans and viruses in networked societies will create a connection. A strategic step to deal with the dynamics of the Covid-19 pandemic threats is the obligation to use masks. Masks can limit the virus' circulation in social environments, especially during face-to-face interaction and communication, as the mouth and nose are vital channels for the virus to enter and spread inside the human body. Researchers recommend the implementation of strategic handling to precisely detect and handle the spread of the virus as early as possible. This strategy is a preventive effort against further severe threats caused by the Covid-19 pandemic. Additional practical handling is required, including the discipline of implementing health protocols, such as wearing masks under the supervision of authorities.